Localization of matrix metalloproteinases in the placenta of cows with complicated pregnancy by placental insufficiency - Avdeenko V.S.; Safronov D.I.; Akhmadov V.T. (BIO Web of Conferences, 2024)
The placenta of 8 cows with physiological (PP) and placental insufficiency pregnancy (FPI) served as the material for the study. Analysis of the content of glycosaminoglycans (GAG) in the tissue of the uterine part of the placenta in cows with FPI indicated the degradation of the connective tissue matrix of cotyledons of chorionic villi and crypts of caruncles, due to the lack of interstitial substance structuring. Hyperplasia of crypts of caruncles is observed, which form glandular-like structures, with reduction in cotyledon chorionic villi in cotyledons. The level of MMP-3 metalloproteinase was detected in the structure of defragmented maternal crypts, and the presence of immunopositive cells was recorded only in the vascular region with active hyperplasia of crypt epithelial cells. The level of MMP-3 metalloproteinase was detected in the structure of defragmented maternal crypts, and the presence of immunopositive cells was recorded only in the vascular region with active hyperplasia of crypt epithelial cells. A decrease in the level of MMP-3 metalloproteinase in cotyledons of placental structures of cows was clearly noted in samples obtained from cows with placental insufficiency (FPI). Morphological changes in the placenta in cows with FPI, manifested before childbirth, are characterized by the free arrangement of cotyledons of chorionic villi in the crypts of caruncles formed by branches of uterine septa. Translocation of metalloproteinases of the MMR-3 type was found in the cotyledon space between the villi of the cotiledon chorion and the epithelium of the crypts of caruncles, especially in places where the villi are completely reduced. The conducted research may contribute to the development of enzyme immunoassay (ELISA) for the diagnosis of reproductive pathologies in mothers and newborns.